Fire history and treeline elevation in the Apennines: insights from pedo-anthracological analysis on Monte Cervati, Southern Italy - Bonanomi, Giuliano; Stinca, Adriano; Amoroso, Giandomenico; Allevato, Emilia; Iacomino, Giuseppina; Mauriello, Gianluigi; Motti, Riccardo; Nicastri, Alfredo; Bellucci, Francesca; Abelouah, Mohamed Rida; Di Costanzo, Luigi; Idbella, Mohamed (Frontiers in Plant Science, 2025)
IntroductionThe treeline elevation in the Apennines is significantly lower than its climatic potential, often attributed to historical anthropogenic disturbances such as fires, logging, and grazing. However, the specific impacts of individual disturbance events, particularly fires, on treeline dynamics remain unclear. This study investigates the relationship between treeline elevation and historical fire events using Monte Cervati (1,899 m a.s.l.) as a model system.LocationMonte Cervati, located in the Apennine Mountains, Italy.MethodsThe current treeline elevation was mapped, and vegetation was characterized. Pedo-anthracological analyses were conducted in a sinkhole near the summit to reconstruct past vegetation and fire history. Charcoal samples from a paleosol layer were identified and dated to determine past fire events and vegetation composition.ResultsThe present treeline, composed exclusively of Fagus sylvatica, is situated at an average elevation of 1,710 m a.s.l., with higher elevations on northern slopes compared to southern ones. The vegetation above the treeline is dominated by small herbaceous species (Plantago subulata), with scattered shrubs such as Daphne oleoides and Juniperus communis. Notably, no F. sylvatica regeneration was observed above the treeline. Pedo-anthracological analysis revealed a charcoal-rich layer within a paleosol at 1,806 m a.s.l., dating back to approximately 4,800 BP. Charcoal analysis identified remains from herbaceous (Dactylis), shrubs (Daphne), and trees (F. sylvatica), indicating that past vegetation consisted of wooded grassland.ConclusionsHistorical fire events likely played a crucial role in shaping the current treeline structure by eliminating the arboreal component and promoting the establishment of a predominantly herbaceous landscape. These findings suggest that fire disturbances have long-term effects on treeline dynamics, potentially contributing to the treeline depression observed in the Apennines today.